The effect of stock splits announcement and implementation to share prices - Ghazali, Zahiruddin; Mustafa, Munauwar; Hasan, Hasnizam; Kassim, Mohd Shah (2000)
This Research tries to clarify the role of stock splits, especially in views of its market effect.Past researches snowed that firms engaged in these exercises record a substantially amount of abnormal returns occurs upon its announcement.This research covers only companies that announced and implemented its stock splits program between 1st January 1980 up to 31st. December 1993.Mean Adjusted Return (MAR)Models is use to validate the significance of the events.Furthermore, Ordinary Least Square-Uni-variate is use to test relationship between Cumulative Average Abnormal Return (CAAR) and prior dividend yield.Test results show there is no significant abnormal returns occur on.However, results confer abnormality in returns during the observed period of stock splits implementations.A change in prior dividend yield, to stock splits announcement significantly correlated to abnormal returns and a similar occurrence were viewed with split implementation.Lastly, ever increasing CAAR, before the announcement or implementation to stock splits, indicate an information leakage and information discount by the market